ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT INVESTASI PASAR MODAL SYARIAH PADA MAHASISWA FEBI UIN STS JAMBI - MUHAMMAD IRFAN; TITIN AGUSTIN NENGSIH; MUHAMMAD ISMAIL (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study is entitled Analysis of the Factors Influencing Interest in Islamic Capital Market Investment in FEBI Students at UIN STS Jambi. The aims of this study are: 1) To explain the effect of motivation on the interest in investing in the Islamic capital market in students of the Faculty of Islamic Economics and Business, UIN STS Jambi. 2) To explain the effect of Return on interest in investing in the Islamic capital market in students of the Faculty of Economics and Islamic Business, UIN STS Jambi. 3) To explain the effect of Capital Market Literacy on the interest in investing in the Islamic capital market in students of the Faculty of Economics and Islamic Business, UIN STS Jambi. 4) To explain the effect of Capital Market Motivation, Return and Literacy on the interest in investing in the Islamic capital market in students of the Islamic Economics and Business Faculty of UIN STS Jambi. The research method used by researchers is a quantitative approach. The results of this study are: 1) From the results of the regression test it is found that partially motivation has a significant effect on the interest in investing in the Islamic capital market in students of the Faculty of Economics and Islamic Business, UIN STS Jambi. 2) From the results of the regression test it was found that partially Return had a significant effect on the Interest in Investing in the Islamic capital market in students of the Faculty of Islamic Economics and Business, UIN STS Jambi. 3) From the results of the regression test it was found that partially Capital Market Literacy has a significant effect on the Interest in Investing in the Islamic capital market in students of the Faculty of Islamic Economics and Business, UIN STS Jambi. 4) Simultaneously, Motivation, Return and Capital Market Literacy have a significant effect on the Interest in Investing in the Islamic capital market in students of the Faculty of Islamic Economics and Business, UIN STS Jambi.